Fat .sub.max as an index of aerobic exercise performance in mice during uphill running - Ishihara, Kengo; Taniguchi, Hirokazu (PloS one, 2018)
Endurance exercise performance has been used as a representative index in experimental animal models in the field of health sciences, exercise physiology, comparative physiology, food function or nutritional physiology. The objective of the present study was to evaluate the effectiveness of Fat.sub.max (the exercise intensity that elicits maximal fat oxidation) as an additional index of endurance exercise performance that can be measured during running at submaximal exercise intensity in mice. We measured both Fat.sub.max and Vo.sub.2 peak of trained ICR mice that voluntary exercised for 8 weeks and compared them with a sedentary group of mice at multiple inclinations of 20, 30, 40, and 50° on a treadmill. The Vo.sub.2 at Fat.sub.max of the training group was significantly higher than that of the sedentary group at inclinations of 30 and 40° (P < 0.001). The running speed at Fat.sub.max of the training group was significantly higher than that of the sedentary group at inclinations of 20, 30, and 40° (P < 0.05). Blood lactate levels sharply increased in the sedentary group (7.33 ± 2.58 mM) compared to the training group (3.13 ± 1.00 mM, P < 0.01) when running speeds exceeded the Fat.sub.max of sedentary mice. Vo.sub.2 at Fat.sub.max significantly correlated to Vo.sub.2 peak, running time to fatigue, and lactic acid level during running (P < 0.05) although the reproducibility of Vo.sub.2 peak was higher than that of Vo.sub.2 at Fat.sub.max . In conclusion, Fat.sub.max can be used as a functional assessment of the endurance exercise performance of mice during submaximal exercise intensity.